A possible role of WNT5A expression in papulosquamous skin diseases - Laila Mansour Mohamed; Eiman Adel Hasby; Hagar Ahmed Kassem; Nashwa Naeem Elfar (Indian Journal of Dermatopathology and Diagnostic Dermatology, 2020)
Background: Wnt genes code for a family of secreted, lipid-modified glycoproteins. Wnt5a has important functions in cell proliferation, fate determination, and differentiation. Dysregulation of Wnt5a signaling implicated in multiple disease. Aim of Work: The aim is to elucidate the possible role of Wnt5a in pathogenesis of papulosquamous skin disorders through the evaluation of its expression immunohistochemically. Patients and Methods: This study included 80 patients with various papulosquamous diseases (psoriasis, lichen planus, ptyriasis rosea, and ptyriasis rubra pilaris), in addition to 20 healthy controls served as control. Punch skin biopsies were taken from all individuals for immunohistochemical staining with Wnt5a. Results: There was a highly statistically significant upregulation in Wnt5a expression in all stained skin specimens of the studied papulosquamous diseases in both epidermis and dermal lymphocytes compared to normal control. Conclusion: The upregulated expression of Wnt5a indicated its involvement in pathogenesis of papulosquamous diseases. Wnt5a and/or its receptor can be a challenging target for therapeutic intervention. Regular follow-up for these patients is recommended as Wnt5a also may be involved in their malignant transformation.